1993
DOI: 10.3354/meps097031
|View full text |Cite
|
Sign up to set email alerts
|

Daily course of photosynthesis and photoinhibition in marine macroalgae investigated in the laboratory and field

Abstract: Photoinhibition of photosynthesis and its recovery was investigated in the laboratory and in the field with fluorescence and oxygen measuring devices. Photosynthetic efficiency measured at non-saturating fluence rates and the ratio of variable fluorescence to maximal fluorescence (FJF,) showed an approximately inverse course compared to the fluence rate of daylight measured continuously during the day. In the morning photosynthetic efficiency was high, but decreased with increasing fluence rate. Maximal phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(102 citation statements)
references
References 5 publications
8
92
0
Order By: Relevance
“…This is supported by the changes in the violaxanthin/zeaxanthin ratios at midday in both the field and laboratory and by changes due to xanthophyll cycling previously observed in this alga (Gevaert et al 2002). This type of photoinhibition is characterized by a quick recovery, and is in agreement with other studies on brown macrophytes (Hanelt et al 1993, Hanelt 1998. The L. saccharina in our laboratory study exposed to UV-B irradiances in addition to PAR and UV-A displayed components of both dynamic and chronic photoinhibition.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is supported by the changes in the violaxanthin/zeaxanthin ratios at midday in both the field and laboratory and by changes due to xanthophyll cycling previously observed in this alga (Gevaert et al 2002). This type of photoinhibition is characterized by a quick recovery, and is in agreement with other studies on brown macrophytes (Hanelt et al 1993, Hanelt 1998. The L. saccharina in our laboratory study exposed to UV-B irradiances in addition to PAR and UV-A displayed components of both dynamic and chronic photoinhibition.…”
Section: Discussionsupporting
confidence: 80%
“…These studies have largely been short-term studies on UV-R effects on photosynthesis, specifically photoinhibition, based on active fluorescence or oxygen-flux measurements (Brouwer et al 2000, Karsten et al 2001. Other studies have differentiated between chronic and dynamic photoinhibition in macrophytes (Hanelt et al 1993, Franklin & Forster 1997, Hanelt 1998, while long-term studies on the effects of UV-R on macrophyte growth have also been documented (Michler et al 2002). Fewer studies on the effects of UV-R have been conducted on temperate populations of macrophytes (Wood 1987, Dring et al 1996b, Gevaert et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The second, chronic photoinhibition is associated with much more severe damage to PSII, recovers extremely slowly, and is interpreted as photon damage. Although dynamic photoinhibition occurs widely in phytoplankton , macroalgae (Hanelt et al 1993;Franklin et al 1996), and corals (Brown et al 1999;Hoegh-Guldberg and Jones 1999;Ralph et al 1999; this study), signs of chronic photodamage have previously been observed only in corals exposed to elevated temperatures (Jones et al 1998;Warner et al 1999) or intertidal corals under solar bleaching (Brown et al 2000). Our data on a number of shallow corals clearly suggest that the daily exposure to full sunlight leads to chronic photoinhibition, even at moderate temperatures (24-29ЊC).…”
Section: Discussionmentioning
confidence: 96%
“…So in an ecological perspective, photoinhibition of aquatic macrophyte communities in their natural habitat should not be very important. It is, however, possible that the upper phytoelements in the canopy can be inhibited (e.g., Huppertz et al 1990;Hanelt et al 1993), whereas the unused photosynthetic potential of the lower layers of phytoelements compensates for this inhibition such that the overall community production continues to rise up to the highest incident irradiances. Bleaching of the upper leaves in tropical seagrass canopies exposed to high temperatures in shallow lagoons under the burning sun shows that photodamage must occasionally be considered.…”
Section: Discussionmentioning
confidence: 99%